PENENTUAN HARGA POKOK PRODUK DAN PENERAPAN COST PLUS PRICING METHOD DALAM PENENTUAN HARGA JUAL PADA RUMAH MAKAN IKAN BAKAR DABU-DABU LEMONG - Moniung, Jennifer T. M; Tinangon, Jantje J.; Kalalo, Meily Y. B (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
Determination of the selling price is very influential to maintain the continuity of a company. The selling price offered by the company must be right, because if the selling price offered is too high then the consumer will think twice and switch to another company, and vice versa if the price offered is too low then the costs incurred by the company cannot be covered even will loss. Cost-plus pricing is one of the methods used in determining the price of a product or service to be sold. Cost-plus pricing is a method of determining selling prices by adding expected profits above the full future costs of producing and marketing products. The aim of this research is to find out the Determination of the Cost of Products and the Implementation of the cost plus pricing method in the Determination of the Selling Price in the Dabu-Dabu Lemong Grilled Fish Restaurant. The results showed that there were differences in the analysis results between the two approaches in the cost plus pricing method. The final analysis results obtained, the selling price formed by variable costing is higher than the full costing approach. But when viewed from the cost of production, the variable costing approach produces a lower value compared to full costing. The selling price set by the current owner has a difference if calculated using the cost plus pricing method. Broadly speaking, the selling price set by the current owner is not a favorable price when compared to the selling price calculated.